2017
DOI: 10.1016/j.molcel.2017.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Autogenous Control of 5′TOP mRNA Stability by 40S Ribosomes

Abstract: Ribosomal protein (RP) expression in higher eukaryotes is regulated translationally, through the 5′TOP sequence. This mechanism evolved to more rapidly produce RPs on demand in different tissues. Here we show that 40S ribosomes, in a complex with mRNA binding protein LARP1, selectively stabilize 5′TOP mRNAs, with disruption of this complex leading to induction of the impaired ribosome biogenesis checkpoint (IRBC) and p53 stabilization. The importance of this mechanism is underscored in 5q− syndrome, a macrocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
112
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(120 citation statements)
references
References 46 publications
(87 reference statements)
7
112
0
1
Order By: Relevance
“…PTBP1 is known as a binding factor for TOP mRNA, which contains 5' terminal oligopyrimidine tract (5'TOP) mostly found in mRNAs encoding ribosomal protein and elongation factors (Avni et al, 1997;Meyuhas, 2000), to regulate translation of the target TOP mRNA (Gismondi et al, 2014) as a cis-acting regulator . LARP1, which is known as 5'TOP mRNA binding proteins, stabilize the target 5'TOP mRNAs by forming complex with 40S ribosome subunit (Gentilella et al, 2017), In this study, SINEUP-GFP showed direct interaction with 40S, implying that SINEUP RNA with multimerization including PTBP1, 40S and the target mRNA may contribute the target mRNA stabilization. There are several reports that PTBP is recruited to cap-independent translation to stimulate translational initiation with re-modelling the target transcripts followed by supplying the small subunit (40S) to binding sites (Caceres et al, 2016;Stoneley & Willis, 2004).…”
Section: Discussionmentioning
confidence: 57%
“…PTBP1 is known as a binding factor for TOP mRNA, which contains 5' terminal oligopyrimidine tract (5'TOP) mostly found in mRNAs encoding ribosomal protein and elongation factors (Avni et al, 1997;Meyuhas, 2000), to regulate translation of the target TOP mRNA (Gismondi et al, 2014) as a cis-acting regulator . LARP1, which is known as 5'TOP mRNA binding proteins, stabilize the target 5'TOP mRNAs by forming complex with 40S ribosome subunit (Gentilella et al, 2017), In this study, SINEUP-GFP showed direct interaction with 40S, implying that SINEUP RNA with multimerization including PTBP1, 40S and the target mRNA may contribute the target mRNA stabilization. There are several reports that PTBP is recruited to cap-independent translation to stimulate translational initiation with re-modelling the target transcripts followed by supplying the small subunit (40S) to binding sites (Caceres et al, 2016;Stoneley & Willis, 2004).…”
Section: Discussionmentioning
confidence: 57%
“…There are tendencies that Torin1 treatment resulted in slight upregulation of TOP mRNAs, and in contrast, downregulation of nonTOP mRNAs ( Supplementary Fig.5b). Besides, TOP mRNA levels were decreased by LARP1 KD, likely indicating RNA destabilization as has been suggested ( Supplementary Fig.5b) [3][4][5] . LARP1 KD did not affect nonTOP RNA abundance.…”
supporting
confidence: 57%
“…In multicellular organisms, since it is the only known sequence element conserved among all RP genes, the 5'TOP motif is considered a key regulatory element for the coordinated control of RP synthesis. Previous studies suggest that the TOP motif provides control of both the transcription of TOP-genes (Parry et al, 2010;Shibui-Nihei et al, 2003) and the translation of TOP-mRNAs (Fonseca et al, 2018;Gentilella et al, 2017;Hamilton et al, 2006;Lahr et al, 2017;Meyuhas and Kahan, 2015;Patursky-Polischuk et al, 2014). A linear correlation of the activity of the luciferase reporters containing the Rpl28 promoter and the abundance of their transcripts (Fig.…”
Section: Discussionmentioning
confidence: 99%